Localization for Outdoor Mobile Robot Using LiDAR and RTK-GNSS/INS - Thepsit, Thitipong; Konghuayrob, Poom; Saenthon, Anakkapon; Yanyong, Sarucha (My University, 2024)
Two types of sensors, light detection and ranging (LiDAR) and real-time kinematic of global navigation satellite system with inertial navigation system (RTK-GNSS/INS), are used for the localization of outdoor mobile robots. However, using LiDAR and RTK-GNSS/INS independently was found to be insufficient for achieving precise positioning. Therefore, a sensor fusion approach based on an adaptive-network-based fuzzy inference system (ANFIS) was implemented to enhance reliability. In this research, data from both sensors were collected to create a dataset for training with ANFIS. The findings indicated that the model derived from the fusion of these two sensors provided results that were much closer to the actual values obtained using each sensor independently. The result demonstrated the effectiveness of the ANFIS-based fusion method in terms of improving the accuracy and reliability of the positioning system for outdoor mobile robots.
Keywords: autonomous mobile robot; fusion sensor; localization; neural fuzzy interface; odometry